2012
DOI: 10.1890/11-1610.1
|View full text |Cite
|
Sign up to set email alerts
|

Transcending scale dependence in identifying habitat with resource selection functions

Abstract: Multi-scale resource selection modeling is used to identify factors that limit species distributions across scales of space and time. This multi-scale nature of habitat suitability complicates the translation of inferences to single, spatial depictions of habitat required for conservation of species. We estimated resource selection functions (RSFs) across three scales for a threatened ungulate, woodland caribou (Rangifer tarandus caribou), with two objectives: (1) to infer the relative effects of two forms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
277
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(298 citation statements)
references
References 80 publications
15
277
0
Order By: Relevance
“…This suggests that anthropogenic pressures affect habitat selection at a home‐range level, whilst environmental variables influence site‐level habitat selection (Boyce, 2018; DeCesare et al., 2012). A similar result was found for brown bears ( Ursus arctos ) in the Cantabrian Range, northwest Spain (Sánchez, Cushman, & Saura, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that anthropogenic pressures affect habitat selection at a home‐range level, whilst environmental variables influence site‐level habitat selection (Boyce, 2018; DeCesare et al., 2012). A similar result was found for brown bears ( Ursus arctos ) in the Cantabrian Range, northwest Spain (Sánchez, Cushman, & Saura, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Because selection patterns can change across scales (DeCesare et al 2012), it is imperative to understand the relationship between patterns observed at multiple spatiotemporal scales.…”
Section: Discussionmentioning
confidence: 99%
“…The scale-dependent hierarchy of landscape-organism interaction has been documented in light of predation risk and human disturbance [27,69]. Conversely, the scaling-up hypothesis suggests that fine-scale drivers are linked to the observations occurring at coarse scales [70].…”
Section: Choices Made When Building Modelsmentioning
confidence: 99%
“…For example, the use of patches by caribou (Rangifer tarandus) has been linked to both the intrinsic characteristics of a patch and those of the surrounding matrix [26]. In this case, the use of the PMM incorporates analysis at different scales, which is important for species that respond to disturbance at multiple scales [27]. The PMM also provides results (e.g., patch sizes necessary for habitat use) that can be directly applied to land and resource management.…”
Section: Introductionmentioning
confidence: 99%